Fear potentiation is associated with hypothalamic–pituitary–adrenal axis function in PTSD - Jovanovic, Tanja; Norrholm, Seth D.; Blanding, Nineequa Q.; Phifer, Justine E.; Weiss, Tamara; Davis, Michael; Duncan, Erica; Bradley, Bekh; Ressler, Kerry (Psychoneuroendocrinology, 2010)
A central problem in posttraumatic stress disorder (PTSD) is the inability to suppress fear under safe conditions. We have previously shown that PTSD patients cannot inhibit conditioned fear. Another relevant finding in PTSD is the hypersensitivity of the hypothalamic–pituitary–adrenal (HPA) axis feedback. Given their common neurobiological pathways, alterations in HPA function in PTSD may be associated with impaired fear inhibition. The present study examined the relationship between HPA axis function and fear-potentiated startle and inhibition of conditioned fear in trauma-exposed individuals. We used a conditional discrimination procedure (AX+/BX−), in which one set of shapes (AX+) was paired with aversive airblasts to the throat (danger signal), and the same X shape with a different shape (BX−) were presented without airblasts (safety signal). The paradigm also included a transfer of fear inhibition test (AB). In addition to fear-potentiated startle, blood was drawn for neuroendocrine analysis and the dexamethasone suppression test (DEX) was performed; cortisol and ACTH were assessed at baseline and post-DEX. Ninety highly traumatized individuals recruited from Grady Hospital in Atlanta, GA participated in the study. The sample was divided into those who met DSM-IV criteria for PTSD ( n = 29) and Non-PTSD controls ( n = 61) using the PTSD symptom scale (PSS). Both groups showed significant reduction in cortisol and ACTH levels after DEX. Subjects with PTSD had higher fear-potentiated startle to the safety signal, BX− ( F(1,88) = 4.44, p < 0.05) and fear inhibition trials, AB ( F(1,88) = 5.20, p < 0.05), both indicative of less fear inhibition in the presence of B, compared to control subjects. In addition, fear-potentiated startle to AX+, BX−, and AB was positively correlated with baseline and post-DEX ACTH in PTSD subjects. These results suggest that impaired fear inhibition and associated alterations in HPA feedback may reflect amygdala hyperactivity in subjects with PTSD.